Treatment of open tibial shaft fractures using intra medullary interlocking - Reddy, G. Ramachandra; Prasad, P. N. (International Journal of Research in Orthopaedics, 2017)
Background: It has been estimated that annual incidence of open fractures of long bones is 11.5 per 100 000 personswith 40% occurring in the lower limb and commonest site is the tibial diaphysis. This study was performed to evaluate clinical outcome of patients with open fracture of shaft of tibia. Methods: It was a hospital based observational prospective study was performed on a total of 30 study participants were enrolled and out of them 2 were lost to follow up. After discharge follow up was done every four weeks for clinical, radiological progress of bony union and soft tissue healing. Results: Majority of the study participants were in the age group of 31-40 years (37%). Males were the main study participant (63.3%). The process of healing took for about 13-16 weeks in 57.1% of the study participants were as in 18% of them it healed within 12 weeks. In 25% of the study participants the healing was completed in more than 16 weeks. Conclusions: It has been observed from the study that interlocked intramedullary nailing is a very effective and safe and technique for the management of open tibial fractures.